Juan Mayorga's "Phaedra": text and performance - Barrero Pérez, Óscar (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
Juan Mayorga premiered in 2007 his version of Phaedra,basically based on Hippolytusby Euripides. The deviation of this new Phaedrawith respect to the tradition of the myth is not very relevant, but it is worthwhile in ending. The staging of the performance was given to understand a falling in love of Hippolytus that is not included in the text, which leads to raise, once again, the differences between a theatrical literary text and its performance. Or those who can be between the theatre writing of an author and the liberal interpretation of whom performs the play.
Keywords: Juan Mayorga; Phaedra; Theatrical text; Theatrical performance